Multi-external-chamber coaxial borehole heat exchanger: Dynamic heat transfer and energy consumption analysis. (1st March 2020) - Li, Yang; Ma, Ling; Xu, Wenjie; Zhu, Qiang; Li, Wenjia; Zhao, Jun; Zhu, Jiebei
Highlights: Dynamic heat transfer and energy consumption characteristics are analyzed. Numerical model and analytical model are integrated to analyze long-term operation. Field experiment with a 235 m deep heat exchanger was performed. Number of borehole heat exchangers can be reduced by 13.33%. Energy consumption of the water pump can be reduced by 28.16%. Abstract: The borehole heat exchanger (BHE) is a key component of a ground-coupled heat pump (GCHP) system, and its heat transfer performance strongly influences the entire system. This study aims to evaluate the dynamic heat transfer characteristics of a multi-external-chamber coaxial (MECC) BHE, and compared to a conventional double U-tube (2U) BHE. A three-dimensional numerical model was established and validated by a field experiment. The effects of several key design and operating parameters on heat transfer were investigated, and a sensitivity analysis was performed. The effect of groundwater flow on heat transfer was investigated using a modified three dimensional model. Case studies including comprehensive energy consumption analysis were carried out for two optimization objectives, based on the three-dimensional model coupled with a pulse-load finite line source model. The results indicate that the maximum and average heat transfer rate of the MECC BHE can be increased by 65.2% and 10.32% compared with the 2U BHE. An optimized design for deep application was performed in which the optimal flow direction and optimal insulation length ratio were included. For case studies conducted with 2U BHE, applying MECC BHE instead can reduce the BHE number by 13.3%, or the energy consumption of the water pump and the entire system by 28.16% and 9.66%, respectively.